On the Scale of "Simultaneous" Influence of Several "Hot" Particles on the Conditions of Heat and Mass Transfer at Ignition of Liquid Condensed Substance; Journal of Engineering Thermophysics; Vol. 18, iss. 4 - Kuznetsov G. V. Geny Vladimirovich (2009, 2009)
Title screen